The Effectiveness of Write-to-Learn Social-Oriented-Scientific-Issues on Students’ Critical Thinking and Argumentation Skills - Rahma Yuliyani; Asep Mulyani; Nurul Azmi; Edy Chandra (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
This research aimed to analyze the effectiveness of Write-to-Learn-Social-Oriented-Scientific-Issues' on the critical thinking and argumentation skills of grade eleven students. The study employed a quantitative approach and a quasi-experimental method and involved static groups of pretest-posttest design with two experimental classes. The strategies of the Write-to-Learn-Social-Oriented Scientific Issues were divided into two: Free and Guided Write-to-Learn. These strategies were implemented in each class. The Hotelling’s Trace test showed that the strategy was less effectively implemented on students' critical thinking skills than on students' argumentation skills. Furthermore, the hypothesis test using the independent sample t-test showed that the Free Write-to-Learn-Social-Oriented-Scientific-Issue strategy effectively built students' critical thinking skills and argumentative abilities to learn biology. Meanwhile, the Guided strategy was less effectively implemented on critical thinking skills but was effectively applied to students' argumentation skills to understand biology.